Entomopathogenic fungus Beauveria bassiana–based bioinsecticide suppresses severity of powdery mildews of vegetables by inducing the plant defense responses - Iida, Yuichiro; Higashi, Yumiko; Nishi, Oumi; Kouda, Mariko; Maeda, Kazuya; Yoshida, Kandai; Asano, Shunsuke; Kawakami, Taku; Nakajima, Kaori; Kuroda, Katsutoshi; Tanaka, Chiharu; Sasaki, Ayano; et al. (Frontiers in Plant Science, 2023)
The entomopathogenic fungus Beauveria bassiana is used commercially as a microbial insecticides against a wide range of agricultural insect pests. Some strains of B. bassiana protect the plants from pathogens, but the underlying mechanism(s) by are largely unknown. Here, we found that prophylactic sprays of commercial bioinsecticide Botanigard on cucumber, tomato, and strawberry plants suppressed the severity of economically damaging powdery mildews. On leaf surfaces, hyphal elongation and spore germination of cucumber powdery mildew, Podosphaera xanthii, were inhibited, but B. bassiana strain GHA, the active ingredient isolated from Botanigard, only inhibited hyphal elongation, but had no effect on spore germination of P.xanthii. Additionally, strain GHA suppressed powdery mildew symptoms locally, not systemically. Co-treatment with Botanigard and strain GHA induced a hypersensitive response (HR)-like cell death in epidermal cells of cucumber leaves in a concentration-dependent manner and inhibited penetration by P. xanthii. Transcriptome analysis and mass spectrometry revealed that GHA induced expression of salicylic acid (SA)-related genes, and co-treatment with Botanigard and GHA increased the SA level in cucumber leaves. In NahG-transgenic tomato plants, which do not accumulate SA, the biocontrol effect of tomato powdery mildew by GHA was significantly reduced. These results suggested that B. bassiana GHA induces SA accumulation, leading to the induction of HR-like cell death against powdery mildew and subsequent suppression of fungal penetration. Botanigard thus has the potential to control both insect pests and plant diseases.